If f(x) has a constant term of -4 and h(x) has a constant term of 3, then g(0) is -3 ÷ 4.
It is an equation that is based on several input variables to determine the output based on the input variables.
The price of y apples will be $xy if the price of one apple is $x.
The result in this case is the overall cost, which is dependent on the variables x and y as previously demonstrated.
All of the equations are polynomial functions, hence linear exponents will be used to organize the variables and constants.
Then,
The constant term of f(x) is equal to -4, which is the term that is independent of all variables.
In mathematics, f(0) = 4.
The reason for this is that when x = 0, all of the variable terms disappear, leaving just the constant term.
H(x) has a constant term of 3, which is a term that is independent of all variables.
Mathematically,
h(0) = 3
h(x) = f(x) × g(x)
h(0) = f(0) × g(0)
3 = −4 × g(0)
g(0) = -3 ÷ 4
Learn more about the polynomial functions at
https://brainly.com/question/12976257?referrer=searchResults
#SPJ4